Factors influencing customer’s buying intention towards online food application services / Muhammad Fadris Mohd Zamri - Mohd Zamri, Muhammad Fadris (Faculty of Business and Management, 2018)
The primary attempt on this study is to examine the behavioural intention of use on using the food online application services at Petaling Jaya (Seksyen 52), Selangor. This study identify the relationship between four factors which contains privacy and security, perceived usefulness, perceived ease of use and attitude towards behaviour that could able to influence the behavioural intention of using the food online application services. This study also tries to find out the most factors that influencing the behavioural intention of use in food online application service in Petaling Jaya (Seksyen 52) area. In order to perform the statistical data and analysis, a software is being used which is the Statistical Packages for the Social Science (SPSS) version 20 was used. By using the software, the researcher able to identify the result and test the reliability of the questions given, the descriptive statistic especially based on demographic, the relationship between each of the variable and the most variable factor on behavioural intention of use among people using food online application services. The respondent for this study total 111 of citizen in Petaling Jaya (Seksyen 52) which focus more on the person who aged between 18 until 49 years old. All respondent will be responding from the questionnaire given in order to get the result. This study using descriptive research to collect the information that can be related with the behavioural intention of use among people in using the food online application services.